Clinical Potential of Himalayan Herb Bergenia ligulata: An Evidence-Based Study - Shubhadeep Roychoudhury; Dipika Das; Sandipan Das; Niraj Kumar Jha; Mahadeb Pal; Adriana Kolesarova; Kavindra Kumar Kesari; Jogen C. Kalita; Petr Slama (Molecules, 2022)
Herbal products have been used in traditional systems of medicine and by ethnic healers for ages to treat various diseases. Currently, it is estimated that about 80% of people worldwide use herbal traditional medicines against various ailments, partly due to easy accessibility and low cost, and the lower side effects they pose. Bergenia ligulata, a herb ranging from the Himalayas to the foothills, including the north-eastern states of India, has traditionally been used as a remedy against various diseases, most prominently kidney stones. The medicinal properties of B. ligulata have been attributed to bergenin, its most potent bioactive component. Apart from bergenin, the other compounds available in B. ligulata are arbutin, gallic acid, protocatechuic acid, chlorogenic acid, syringic acid, catechin, ferulic acid, afzelechin, paashaanolactone, caryophyllene, 1,8-cineole, β-eudesmol, stigmasterol, β-sitosterol, parasorbic acid, 3-methyl-2-buten-1-ol, phytol, terpinen-4-ol, tannic acid, isovalaric acid, avicularin, quercetin, reynoutrin, and sitoinoside I. This review summarizes various medicinal properties of the herb, along with providing deep insight into its bioactive molecules and their potential roles in the amelioration of human ailments. Additionally, the possible mechanism(s) of action of the herb’s anti-urolithiatic, antioxidative, antipyretic, anti-diabetic, anti-inflammatory and hepatoprotective properties are discussed. This comprehensive documentation will help researchers to better understand the medicinal uses of the herb. Further studies on B. ligulata can lead to the discovery of new drug(s) and therapeutics for various ailments.